Systematic Review of Prevalence Studies and Familial Aggregation in Vestibular Migraine - Paz-Tamayo, Ana; Perez-Carpena, Patricia; Lopez-Escamez, Jose A. (Frontiers in Genetics, 2020)
Background: Vestibular migraine (VM) is complex disorder consisting of episodes of migraine and vertigo with an estimated prevalence of 1-3%. As migraine, it is considered that VM has genetic predisposition; however, evidence to support a genetic contribution has not been critically appraised. Objective: The aim of this systematic review is to assess available evidence in scientific publications to determine the role of inheritance in VM. Methods: After performing the quality assessment of the retrieved records, 31 studies were included (24 epidemiological reports and 7 genetic association studies in families or case-control in candidate genes). We gathered data about prevalence of VM in different populations and in families, and also about the genetic findings reported. In addition, other variables were considered to assess the heritability of VM, such as the ancestry, the age of onset or the familial history of vertigo and migraine. Results: The estimated prevalence of VM was different between black (3.13%), white (2.64%) and Asian (1.07%) ethnicities. The reported prevalence of VM in migraine patients is higher in European countries (21%) than in Asian countries (10%). Moreover, the prevalence of the migraine-vertigo association in families is 4-10 times higher than in the prevalence reported in the general population (sibling recurrence risk ratio λs=4.31-10.42). We also found that the age of onset is lower in patients with simultaneous onset of symptoms and in those who have familial history for migraine and/or vertigo, suggesting anticipation. Although some genetic studies have reported few allelic variants associated to MV, replication studies are needed to validate these results. Conclusions: The available evidence to support heritability in VM is limited. Variability in prevalence depending on ethnicity and geographic location suggests a combined genetic and environmental contribution to VM. However, the familial aggregation observed in VM support genetic and shared familial environmental effects that remarks the necessity of twins and adoptees-based epidemiological studies to estimate its heritability.